Dichlorido{2-morpholino-N- 1-(2-pyridyl)ethylidene ethanamine-kappa N-3,N ',N ''}manganese(II) - Hisham, N.A.I.; Ali, Hapipah Mohd; Khaledi, H.; Gwaram, N.S. (International Union of Crystallography, 2011)
In the title compound, [MnCl2(C13H19N3O)], the Mn-II ion is pentacoordinated in a distorted square-pyramidal geometry. The coordination environment is defined by the N,N',N ''-tridentate Schiff base ligand and one Cl atom in the basal positions and one Cl atom in the apical position. In the crystal, intermolecular C-H center dot center dot center dot Cl hydrogen bonds link the molecules into a three-dimensional network. An intramolecular C-H center dot center dot center dot Cl hydrogen bond is also observed.